Digitalizing quality assurance in logistics: trends and challenges - Nagy, Gábor; Szentesi, Szabolcs; Varga, Károly Attila (Advanced Logistic Systems - Theory and Practice, 2024)
The rapid advancement of digital technologies has revolutionized logistics networks, offering unprecedented opportunities for enhancing quality assurance. This paper continues the discussion on the role of digitalization in logistics, focusing on the latest technological innovations, implementation challenges, and future trends. By examining the impact of digital tools such as IoT, AI, and blockchain on logistics quality assurance, this paper provides a comprehensive overview of how companies can leverage these technologies to improve operational efficiency and meet the growing demands of the global market. The paper also addresses the challenges associated with digital transformation, including cybersecurity risks and implementation barriers, and proposes strategies for overcoming these obstacles. Finally, the paper explores emerging trends in logistics digitalization and their implications for the future of supply chain management.